Penggunaan Media Flash Card dalam Meningkatkan Kemampuan Literasi Membaca Siswa pada Materi Aku Berperilaku Pancasila di Kelas II SDN 03 Mojo - Fatkhi Fiddin, Abdullah; Purbasari, Imaniar; Rondli, Wawan Shokib (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to determine the effectiveness of using flash card media on the reading literacy skills of second-grade students at SDN 03 Mojo in the topic "Behaving According to Pancasila Values." The study employed a quantitative approach with a Pre-Experimental One Group Pretest-Posttest design. The research subjects consisted of 12 second-grade students. Data collection techniques included interviews, observation, and tests. The results showed a significant difference between the pretest and posttest scores after the implementation of flash card media, with a significance value of 0.000 < 0.05 based on the paired sample t-test. In addition, the gain test results showed an average increase of 0.6478, falling into the medium to high category. These findings demonstrate that flash card media is effective in improving elementary